A new stabilizing regime of tearing mode entrainment in the presence of a static error field. (30th September 2019) - Okabayashi, M.; Inoue, S.; Logan, N.C.; Taylor, N.Z.; Strait, E.J.; de Grassie, J.; Ferraro, N.; Hanson, J.; Jardin, S.; La Haye, R.J.; Liu, Y.Q.; Paz-Soldan, C.; et al.
Abstract: Uncorrected static error fields (EFs) in axisymmetric fusion devices are one of the few remaining serious obstacles for advancing the present tokamak-based approach to a practical reactor. Magnetohydrodynamic tearing modes (TMs) lock to them, causing sudden losses of confinement known as disruptions. Recently, a hypothesis has been proposed that there may exist a self-healing stable regime in which a static resonant EF is effectively shielded by forcing these TMs to slowly rotate inductively by the applied non-axisymmetric field (Inoue et al 2017 Nucl. Fusion 57 116020; Inoue et al 2018 Plasma. Phys. Control. Fusion 60 025003; Inoue et al 2018 Preprint: 2018 IAEA Fusion Energy Conf . TH/P4-24). This is based on non-linear, resistive, reduced magnetohydrodynamic simulations using a cylindrical single helicity model. Proof-of-principle experiments in the DIII-D device showed that the magnetic mode structure on the plasma surface is qualitatively consistent with the simulation prediction. However, radial mode profiles revealed qualitatively different behavior. This led to a revised hypothesis that in actual non-circular toroidal devices, a tearing layer in forced rotation induces a shielding process at other rational surfaces when we take into account multiple resonant Fourier components. The time evolution experiment of the radial penetration is supportive of this hypothesis.